(untitled) (LEARNing Landscapes, 2014)
This article illuminates academic barriers that students with learning disabilities (LD) face in their science classrooms and the ways in which the Universal Design for Learning (UDL) framework can offer practical ways to promote cognitive access to science education. This article also examines current research on intervention-based practices for students with LD in science classrooms. Drawing on the UDL model, the authors offer a framework for science teachers and practitioners to integrate inclusive practices in their teaching for diverse learners.